Influence of Technological Parameters on the Cutting Temperature during Trochoidal Milling - Waszczuk, Kamil Piotr (Manufacturing Technology Journal, 2024)
The aim of the article was to present the results of cutting temperature measurements during trochoidal milling. The investigated material was 145Cr6 (50 HRC). Three trochoidal paths were used: A- described by movement circle, B- described by arcs and straight lines, C- described by short lines between a lot of points. The main conclusions include: similar values of cutting tem-peratures when using paths A and C (differences between the values of about 5%), the use of a trochoidal path type B enables a significant reduction of the cutting temperature. During tro-choidal milling, the maximum temperature values were about 420ºC.
Keywords: Trochoidal milling; Hard machining; Cutting temperature; Tool path